Inkjet‐Printed Piezoelectric Thin Films for Transparent Haptics (Adv. Mater. Technol. 8/2022). Issue 8 (10th August 2022) - Glinsek, Sebastjan; Song, Longfei; Kovacova, Veronika; Mahjoub, Mohamed A.; Godard, Nicolas; Girod, Stéphanie; Biagi, Jean‐Luc; Quintana, Robert; Schleeh, Thomas; Guedra, Matthieu; Rupin, Matthieu; Defay, Emmanuel
Abstract : Transparent Haptics Effectiveness of inkjet printing of piezoelectric thin films for haptic devices is demonstrated in article number 2200147 by Sebastjan Glinsek and co‐workers. A transparent device, based on printed piezoelectric lead zirconate titanate and interdigitated indium tin oxide electrodes, exhibits a standing Lamb wave at 63.3 kHz. At an applied voltage of 100 V, the out‐of‐plane displacement reaches 2 μm, which creates a friction modulation functionality.